When I say it’s fine, it is fine: Functions of Meishi-er (It’s fine) by Mandarin-speakers in conversations - Yuanyuan, Li; Yansheng, Mao (Sinología hispánica. China Studies Review, 2021)
This study aims to investigate the Mandarin-speaker’s use of a frequently occurring responsive marker — Meishi-er (It’s fine) — when interacting in ordinary Chinese scenarios to examine how the use of this marker reflects the speaker’s communicative skills and the characteristics of the interaction. The data consisted of 261 segments of Mandarin conversations which were retrieved from Chinese TV dramas. The results show that Meishi-er is primarily used as a head act and occasionally as a supportive move in the speech act sequence. These uses indicate the collaborative or supportive stance adopted by the speaker, which can help him/her to establish and maintain relationships with his/her counterparts. Second, Meishi-er is primarily used in response to an expression of thanks or an apology, as an expression of consolation, as refusal and self-disclosure avoidance strategies, and a tool for terminating arguments in interpersonal communication, which reflect the speaker’s communicative and social competence. As a rapport-oriented backchannel, Meishi-er has been shown to be one of the preferred responses in communication. In addition, the Mandarin-speaker’s use of Meishi-er not only demonstrates the speaker’s need to cater for facework, but also reflects the particular nature of harmony-driven interaction in ordinary Chinese contexts.